1993
DOI: 10.1103/physrevd.47.3049
|View full text |Cite
|
Sign up to set email alerts
|

Minijets and the behavior of inelasticity at high energies

Abstract: We present an extension of the interacting gluon model, used previously to calculate inelasticities and leading particle spectra in hadronic and nuclear collisions, which incorporate also the production of minijets. As a result we get inelasticity slowly increasing towards some limited value. PACS number(s1: 13.85.Hd, 12.38.Mh, 13.87.CeThe concept of inelasticity plays an important role in cosmic ray and accelerator physics. Whereas in the former it is crucial for the understanding and interpretation of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 11 publications
(17 reference statements)
1
23
0
Order By: Relevance
“…We have presented in this paper a description of the inclusive reaction pp → pX in the whole phase space within the Regge-Mueller formalism, modified by the renormalization of the diffractive cross section. The average multiplicity and the average inelasticity were obtained from the leading proton spectrum and both of them resulted to be increasing functions of energy, in agreement with [4,5] and particularly with [7]. The energy dependence of these quantities is such that allows one to accommodate very well the charged particle multiplicities n ch e + e − and n ch pp by an universal function once an appropriate relation is used.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We have presented in this paper a description of the inclusive reaction pp → pX in the whole phase space within the Regge-Mueller formalism, modified by the renormalization of the diffractive cross section. The average multiplicity and the average inelasticity were obtained from the leading proton spectrum and both of them resulted to be increasing functions of energy, in agreement with [4,5] and particularly with [7]. The energy dependence of these quantities is such that allows one to accommodate very well the charged particle multiplicities n ch e + e − and n ch pp by an universal function once an appropriate relation is used.…”
Section: Discussionsupporting
confidence: 59%
“…The question is that it requires a previous knowledge about the energy dependence of the inelasticity and about the behavior of the average leading particle multiplicity which constitute themselves problematic subjects. In particular, the energy dependence of the average inelasticity is a very much disputed question since there are opposite claims that this quantity increases [4,5,6,7] or that it decreases [8,9,10] with increasing energy at quite different rates. In spite of the of models predicting extreme behaviors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Its original application to the description of inelasticity [12] and multiparticle production processes in hydrodynamical treatments [13] was followed by more refined applications to leading charm production [14] and to single diffraction dissociation, both in hadronic reactions [15] and in reactions originated by photons [16]. These works allowed for providing the systematic description of the leading particle spectra [17] and clearly demonstrated that they are very sensitive to the amount of gluonic component in the diffracted hadron as observed in [18] and [19].…”
Section: A Brief History Of the Igmmentioning
confidence: 99%
“…A very recent and improved analysis by the STAR collaboration has given further support to this picture [15]. A more solid evidence of this phenomenon may come from the study of jets at the Large Hadron Colider (LHC), where the energy released by the nuclear projectiles in the central rapidity region will be larger [16] and so the formed fireball will be larger and live longer, allowing for a more complete study of waves.…”
Section: Introductionmentioning
confidence: 99%